Role of stem cells on motor function recovery in stroke patients: systematic review - Babita Raghuwanshi; Suresh K. Thanneeru; Roshan Chanchalani; Sumit Raj; Pradeep Chouksey; Md Yunus; Amit Agrawal (Egyptian Journal of Neurosurgery)
Abstract Background The effectiveness of stem cell (SC) therapy for motor recovery in stroke patients remains debated within the scientific community. Aim/Objective This study aims to conduct a comprehensive systematic review and meta-analysis to evaluate the therapeutic potential of SC administration for motor recovery in stroke. Methods A thorough search was performed on major electronic databases—PubMed, Scopus, ScienceDirect, and Cochrane—until August 15, 2023. Studies were selected based on predefined inclusion and exclusion criteria to ensure methodological rigor and relevance. Results The initial search identified a substantial number of studies. After applying the selection criteria, a final set of eligible studies was reviewed. The extracted data covered various outcome measures related to motor recovery in stroke patients. Conclusions Although some studies suggest the potential efficacy of stem cell therapy for motor recovery in stroke patients, the evidence lacks consistency. Future well-designed, robust randomized controlled trials are necessary to evaluate the efficacy, safety, and ethical implications of stem cell therapy for motor recovery in stroke patients.